2015
DOI: 10.1159/000369926
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of 368 Patients with Nasal Rosacea: Subtype Classification and Grading of Nasal Rosacea

Abstract: Background: The clinical features of nasal rosacea have not been described in detail. Objective: To describe the clinical features of nasal rosacea. Methods: 599 patients were classified into those with rosacea in both the nasal and extra-nasal areas (group A), localized nasal rosacea (group B) and rosacea without nasal involvement (group C). Results: The mixed subtype was more common in group A (n = 337) than in group C (n = 231). The severity score was higher in group A than in group C. Erythematotelangiecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…6,7 Lee et al 8 reported that 56 (9.3%) out of 599 rosacea patients had rhinophyma during the same period; similarly, in the present study, we diagnosed 39 (9.8%) patients with rhinophyma out of 382 rosacea patients, which was consistent with the previous observations of Lee et al in Asian patients 8 but lower than that observed in Western populations. 6,7 Lee et al 8 reported that 56 (9.3%) out of 599 rosacea patients had rhinophyma during the same period; similarly, in the present study, we diagnosed 39 (9.8%) patients with rhinophyma out of 382 rosacea patients, which was consistent with the previous observations of Lee et al in Asian patients 8 but lower than that observed in Western populations.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 Lee et al 8 reported that 56 (9.3%) out of 599 rosacea patients had rhinophyma during the same period; similarly, in the present study, we diagnosed 39 (9.8%) patients with rhinophyma out of 382 rosacea patients, which was consistent with the previous observations of Lee et al in Asian patients 8 but lower than that observed in Western populations. 6,7 Lee et al 8 reported that 56 (9.3%) out of 599 rosacea patients had rhinophyma during the same period; similarly, in the present study, we diagnosed 39 (9.8%) patients with rhinophyma out of 382 rosacea patients, which was consistent with the previous observations of Lee et al in Asian patients 8 but lower than that observed in Western populations.…”
Section: Discussionsupporting
confidence: 92%
“…Para estos objetivos fueron analizados en forma crítica las distintas clasificaciones disponibles en la literatura y se redactaron las bases para conformar una guía de tratamiento útil al médico y al especialista considerando la bibliografía existente, con medicina basada en la evidencia, de las modalidades terapéuticas de le enfermedad [1][2][3][4][5][6][7][8][9][10][11][12][13] . Se dejaron fuera indicaciones no respaldadas por evidencia científica teniendo sí en consideración que las guías terapéuticas son dinámicas y sin dejar de plantear nuevas indicaciones avaladas científicamente en un futuro.…”
Section: Editorial Científicounclassified
“…The 2002 NRS classification system defines the potential overlap of subtypes. Therefore, a rosacea patient may have two or more subtypes . The potential overlap of subtypes and disease progression among subtypes suggest that ETR, which is considered the initial phase of rosacea, may be accompanied by other subtypes such as PPR and PHY.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a rosacea patient may have two or more subtypes. 2,10,11,13,14 The potential overlap of subtypes and disease progression among subtypes suggest that ETR, which is considered the initial phase of rosacea, may be accompanied by other subtypes such as PPR and PHY. According to rosacea diagnostic criteria, papulopustular eruption can occur with or without remarkable centrofacial erythema.…”
Section: Discussionmentioning
confidence: 99%